1972
DOI: 10.1002/1097-0142(197207)30:1<61::aid-cncr2820300110>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Streptozotocin in the treatment of cancer: Phase II study

Abstract: Streptozotocin (NSC‐85998) was administered to 53 patients at a dose of 1 to 2 g/m2 weekly. Response to therapy could be evaluated in 39 patients. Responses exceeding 50% in magnitude of tumor reduction were noted in three patients; responses of 25–50% were noted in an additional four patients. Responses were noted in two of four patients with islet cell carcinoma, one of four patients with malignant carcinoid, one of two patients with carcinoma of the lung, one of two patients with squamous carcinoma of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1973
1973
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…1,3,5 Streptozocin (streptozotocin) is a nitrosourea alkylating agent that is directly cytotoxic to pancreatic beta cells and has been used to treat humans with unresectable or metastatic islet cell tumors, including insulinomas. [6][7][8] Other diseases in human patients that have responded to streptozocin treatment include carcinoid, Hodgkin' s disease, lymphocytic lymphoma, acute lymphoblastic leukemia, and synovial cell sarco-ma. [6][7][8] The major toxicosis associated with streptozocin treatment in humans is proximal renal tubular necrosis, which is dose related and cumulative.…”
mentioning
confidence: 99%
“…1,3,5 Streptozocin (streptozotocin) is a nitrosourea alkylating agent that is directly cytotoxic to pancreatic beta cells and has been used to treat humans with unresectable or metastatic islet cell tumors, including insulinomas. [6][7][8] Other diseases in human patients that have responded to streptozocin treatment include carcinoid, Hodgkin' s disease, lymphocytic lymphoma, acute lymphoblastic leukemia, and synovial cell sarco-ma. [6][7][8] The major toxicosis associated with streptozocin treatment in humans is proximal renal tubular necrosis, which is dose related and cumulative.…”
mentioning
confidence: 99%
“…The result of chemotherapy is sometimes only a reduction of tumor markers without any objective tumor regression. Some rather favorable results have, however, appeared in the literature: some authors have thus found anti-tumor activity of STZ in metastatic carcinoid tumors (6,23,24) while Schein et al (8) found response only in islet cell carcinomas. Doxorubicin has demonstrated activity in carcinoid patients without heart disease, and also in patients failing to respond to STZ, while cisplatin alone appears to be inactive in such patients (25).…”
Section: Discussionmentioning
confidence: 99%
“…The Adriamycin and streptozotocin in sarcoma 609 significantly higher incidence of leukopenia and especially of thrombocytopenia when the two drugs were combined was unexpected. The significantly more frequent mucositis after the combination was disproportionate in view of the 10% incidence with adriamycin used in this schedule 1 and the single case 12 reported in 290 patients treated with streptozotocin alone.4, 6,8,[10][11][12] These differences may suggest that the therapeutic effects and toxicity of the combination of these drugs are mediated by differing mechanisms. Pharmacokinetic studies in patients on both treatment arms in an attempt to elucidate these differences are reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%